Innovation and Practice of Ideological and Political Teaching in Curriculum Driven by Problem Chains with the Support of Rain Classroom - Yuhuan, Li; Xinyuan, Zhang (Randwick International of Education and Linguistics Science Journal, 2025)
In the new era, the comprehensive advancement of ideological and political education in curricula must address the issue of the "separation between professional education and ideological education." The problem-chain teaching method is an effective approach to implementing the concept of ideological and political education in curricula. This paper takes the ideological and political teaching of the foundational public administration course Strategic Management in Public Sector as an example. It systematically designs and elaborates on how to use the Rain Classroom intelligent teaching platform to develop a problem-chain-driven ideological and political teaching system, providing referenceable teaching methods and practical pathways for advancing ideological and political education in curricula.